Perancangan Penerangan Lampu Pada Windsock Berbasis Internet of Things - Willy Seran, Rizhard; Rossydi, Ahmad; Fadhilah Nugrah, Andi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
The innovation made by the author of "DESIGN OF LIGHTING ON WINDSOCK BASED ON INTERNET OF THINGS" The development of this tool aims to provide a solution to the control cable in the event of a lightning strike that causes grounding and causes corrosion which can damage the control cable. The benefits of developing this tool can make it easier for technicians in terms of repair and maintenance. This type of research method is a design research method. The method of applied research/development of this tool includes planning (planning), implementation (acting), observation (monitoring), and reflection/assessment (reflecting). The location of this research is in Mapanget sub-district, Manado City, North Sulawesi, especially at Sam Ratulangi international airport, Manado. The results of the research are Replacing the control cable which originally used a multi-wire cable planted in the ground to be replaced by wireless using a radio link with the TP-LINK CPE220 Outdoor type which can withstand lightning strikes and make maintenance and repair easier.